A Fundamental Analysis of Public Sector Banks in India - Tiwari, Prakash; Verma, Hemraj (Indian Journal of Finance, 2009)
Banks in India can be categorized into non-scheduled banks and scheduled banks. Scheduled banks constitute of commercial banks and co-operative banks. There are about 67,000 branches of Scheduled banks spread across India. During the first phase of financial reforms, there was a nationalization of 14 major banks in 1969. This crucial step led to a shift from Class banking to Mass banking. Since then, the growth of the banking industry in India has been a continuous process.